To Live or Die: What to Wish at 100 Years and Older - Araújo, Lia; Teixeira, Laetitia; Afonso, Rosa Marina; Ribeiro, Oscar (Frontiers in Psychology, 2021)
Previous research has shown that will to live is a strong predictor for survival among older people, irrespective of age, gender, and comorbidities. However, research on whether life at age 100 is perceived as worth living is limited. The available literature has presented evidence for good levels of positive attitudes and life satisfaction at such an advanced age, but it has also suggested that a longing for death is common. This study aimed to add to the existing data on this matter by exploring centenarians’ will to live and the associated factors. The sample comprised 121 centenarians (mean age, 101 years; SD, 1.63 years), 19 (15.7%) of whom were males, from two centenarian studies (PT100). Answers to open questions were analyzed to identify the centenarians’ will to live and the reasons behind it. Three groups were created (willing to live longer, not willing to live longer, no clear positioning) and further analyzed in terms of sociodemographic characteristics, health status, social functioning, and well-being. Of the total sample, 31.4% expressed willingness to live longer, 30.6% did not, and 38% presented no clear positioning. The presence of the Catholic religion (God) was referred for centenarians in all three groups. Annoyance, uselessness, loss of meaning, disconnection, and loneliness were the most common justifications for being reluctant to live longer. Positive valuation of life and good self-rated health, followed by having a confidante and reduced pain frequency, were the factors associated with being willing to live longer. The results of the study contributed to the understanding of the psychological functioning of individuals with exceptional longevity, particularly concerning the factors behind willingness to live at such an advanced age.